IDENTIFYING COMPLIANCE LEVELS IN SAFETY BELT USAGE IN BANGKINANG CITY, KAMPAR REGENCY - Abdul Kudus Zaini; Khairul Fadhli (PT. Intelek Cendikiawan Nusantara, 2024)
Technology plays a pivotal role in the advancement of automobile production, particularly in enhancing vehicle safety. Effective car design contributes significantly to accident prevention and ensures the protection of both drivers and passengers in the event of collisions. Safety features such as seat belts are crucial in this regard, as they secure occupants inside the vehicle during impacts, thereby minimizing injury. According to AKBP Rido Purba, the extent of legal non-compliance is evident from the high incidence of traffic violations in the Kampar Regency. During the 2022 Lancang Kuning Safety Operation conducted by the Kampar Police Traffic Unit, a total of 669 violations were recorded. Among these, the most frequent violations included failure to wear a helmet (111 cases), failure to use a safety belt (81 cases), driving without a valid license (61 cases), and disregarding road markings and traffic signs (23 cases). This study aimed to assess the compliance level regarding the use of safety belts in Bangkinang City and to identify factors influencing compliance. The research focused on Bangkinang City within Kampar Regency. Samples consisted of 100 respondents selected through accidental sampling. Data collection employed a questionnaire, and analysis utilized the chi-squared test. Findings indicated a high average compliance score of 3.45, suggesting strong adherence to safety belt usage. Factors influencing compliance included internal variables such as knowledge, skills, and experience, alongside external factors like social influences and environmental conditions